Kegiatan Aktualisasi Nilai Pancasila dalam Proses Pembelajaran di Kelas VI Madrasah Ibtidaiyah Perguruan Islam Kabupaten Bandung - Hanuna Huwaida Analez; Muhammad Aditya Raya; Zaky Muhammad Javier; Fatimah Azzahra; Nabilah Nur Aprilia; Muhamad Fikry Ramadhani; Restu Nurafni; Ghazy Nufal Muttaqin; Muhammad Raihan Abdul Malik; Annisa Sri Rahayu; Yani Komariah; Dian Herdiana (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The values of Pancasila in daily life can foster good character and strengthen communal harmony. Indeed, Pancasila's values have proven effective in nurturing mutual respect, reinforcing a sense of unity, and cultivating the habit of deliberation in decision-making. The practical application of these values encourages the emergence of a just societal environment. On this occasion, we, Group 2 from the Pancasila Education course at Sunan Gunung Djati State Islamic University Bandung, carried out an assignment to actualize Pancasila values at Madrasah Ibtidaiyah Perguruan Islam on October 28, 2025, with the material on "The Importance of Pancasila Values in Daily Life." To understand their significance more deeply, we focused on three main foundations that shape the nation's morality and identity: Belief in the One and Only God, a Just and Civilized Humanity, and the Unity of Indonesia. This involved raising awareness that actions such as helping parents, assisting friends, and praying before studying are part of applying these three points of Pancasila in everyday life.